A concept for integrated care pathways for atopic dermatitis—A GA2LEN ADCARE initiative - Torsten Zuberbier; Amir Abdul Latiff; Xenofon Aggelidis; Matthias Augustin; Radu‐Gheorghe Balan; Christine Bangert; Lisa Beck; Thomas Bieber; Jonathan A. Bernstein; Marta Bertolin Colilla; Alejandro Berardi; Anna Bedbrook; et al. (Clinical and Translational Allergy, 2023)
Abstract Introduction The integrated care pathways for atopic dermatitis (AD‐ICPs) aim to bridge the gap between existing AD treatment evidence‐based guidelines and expert opinion based on daily practice by offering a structured multidisciplinary plan for patient management of AD. ICPs have the potential to enhance guideline recommendations by combining interventions and aspects from different guidelines, integrating quality assurance, and describing co‐ordination of care. Most importantly, patients can enter the ICPs at any level depending on AD severity, resources available in their country, and economic factors such as differences in insurance reimbursement systems. Methods The GA2LEN ADCARE network and partners as well as all stakeholders, abbreviated as the AD‐ICPs working group, were involved in the discussion and preparation of the AD ICPs during a series of subgroup workshops and meetings in years 2020 and 2021, after which the document was circulated within all GAL2EN ADCARE centres. Results The AD‐ICPs outline the diagnostic procedures, possible co‐morbidities, different available treatment options including differential approaches for the pediatric population, and the role of the pharmacists and other stakeholders, as well as remaining unmet needs in the management of AD. Conclusion The AD‐ICPs provide a multidisciplinary plan for improved diagnosis, treatment, and patient feedback in AD management, as well as addressing critical unmet needs, including improved access to care, training specialists, implementation of educational programs, assessment on the impact of climate change, and fostering a personalised treatment approach. By focusing on these key areas, the initiative aims to pave the way for a brighter future in the management of AD.